A Review of the Energy Efficiency Improvement in DC Railway Systems - Mihaela Popescu (Energies, 2019)
This study is focused on the topical issue of increasing the energy efficiency in DC railway systems, in the context of global concerns for reducing the CO2 emissions by minimizing the energy consumption and energy loss. The main achievements in this complex issue are synthesized and discussed in a comprehensive review, emphasizing the implementation and application of the existing solutions on concrete case studies. Thus, all specific subtopics related to the energy efficiency are covered, starting with power quality conditioning and continuing with the recovery of braking energy, of which a large part is lost in the classic DC-traction substations. The solutions of onboard and wayside storage systems for the braking energy are discussed and compared, and practical examples are given. Then, the achievements in transforming the existing DC-traction substations in reversible substations with capabilities of power quality improvement are systematically reviewed by illustrating the main results of recent research on this topic. They include the equipment available on the market and solutions validated through implementations on experimental models. Through the results of this extensive review, useful reference and support are provided for the research and development focused on energy efficient traction systems.